The tapuia (re)existence: we are goitacazes, botocudos, aymorés e puris - Paste, Rosana; Lacerda, Felipe (Farol, 2024)
The decolonization is a social agenda. Every movement which keeps us (re)writing our history is urgent and necessary. The body and the spirit, tired of so many colonial years, have naturalized and do not always feel the effects of this barbarian crime. This article’s approach is about our native people’s micro history, reframing their way of life and their costumes. Successive lays of aggression lead us to realize how until this day this movement repeats itself when we dialogue with contemporary production of visual artist Felipe Lacerda.